m6A Reader Igf2bp1 Regulates the Inflammatory Responses of Microglia by Stabilizing Gbp11 and Cp mRNAs - Ding, Lu; Wu, Huiran; Wang, Yi; Li, Yun; Liang, Zhanping; Xia, Xiaohuan; Zheng, Jialin C. (Frontiers in Immunology, 2022)
Microglia are brain resident cells that function as brain phagocytic macrophages. The inflammatory responses of microglia induced by pathologic insults are key regulators in the progression of various neurological disorders. Currently, little is known about how these responses are regulated intrinsically. Here, it is observed that LPS-activated microglia exhibit distinct N6-methyladenosine (m6A) methylation patterns that are positively correlated with the expression patterns of corresponding mRNAs. High-throughput analyses and molecular studies both identified Igf2bp1 as the most significantly regulated m6A modifiers in activated microglia. Perturbation of function approaches further indicated Igf2bp1 as a key mediator for LPS-induced m6A modification and microglial activation presumably via enhancing the m6A methylation and stability of Gbp11 and Cp mRNAs. Thus, our study provides a possible mechanism for the m6A methylation-mediated microglia regulation and identifies Igf2bp1 as a potential target for modulating the inflammatory responses of microglia.